Key factors influencing the success of al-Quran memorization among tahfiz students - Mohammad Haafiz Aminuddin Mohd Azmi,; Nik Ahmad Mumtaz Nik Din,; Mohammad Ibrahim Md Khalis,; Haizuran Mohd Jani,; Muhamad Razif Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The tahfiz Quran institution in this country serves as a national human capital development entity. This institution addresses the community’s regard for the Quran as a life guide. This institution cultivates tahfiz students capable of competing with their mainstream counterparts. However, some tahfiz Quran students face challenges and obstacles in memorizing the Quran, as their level of memorization at tahfiz schools in Pahang is relatively low. The purpose of this study is to examine the variables that influence the performance and success of tahfiz students in memorizing the Quran. This study adopts a qualitative approach, with data collected through interviews with five principals (Mudir) of madrasah tahfiz in Pahang to provide an in-depth understanding of their experiences and challenges in managing these institutions. In this study, thematic analysis was conducted to identify key themes. The results of the study show that there are several crucial factors that influence a student’s success in memorizing the Quran, such as personal motivation, family and teacher support, effective memorization strategies, a conducive learning environment, and adherence to religious practices. This study emphasizes the importance of understanding these factors to improve the performance of tahfiz Quran students and contribute to a more structured approach to training excellent tahfiz Quran students.